2008
DOI: 10.1002/art.23288
|View full text |Cite
|
Sign up to set email alerts
|

Absence of posttraumatic arthritis following intraarticular fracture in the MRL/MpJ mouse

Abstract: Objective. Posttraumatic arthritis is a frequent long-term complication of intraarticular fractures. A model of a closed intraarticular fracture in C57BL/6 mice that progresses to posttraumatic arthritis has been developed. The MRL/MpJ mouse has shown unique regenerative abilities in response to injury. The objective of this study was to determine if the MRL/MpJ mouse is protected from posttraumatic arthritis after intraarticular fractures.Methods. Intraarticular fractures were created in MRL/MpJ mice and C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
127
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 52 publications
(59 reference statements)
8
127
0
Order By: Relevance
“…Since that time, there have been many reports showing that multiple tissue types in MRL mice display healing responses. These include heart myocardium (Leferovich et al, 2001;Haris Naseem et al, 2007;Alfaro et al, 2008), digits (Chadwick et al, 2007;Gourevitch et al, 2009), articular cartilage (Fitzgerald et al, 2008;Rai et al, 2012), intra-articular fractures (Ward et al, 2008), corneal epithelium (Ueno et al, 2005), CNS stem cells and tissue (Hampton et al, 2004;Baker et al, 2006;Balu et al, 2009;Thuret et al, 2009), central and peripheral nerves (Buckley et al, 2011;Thuret et al, 2012) and myometrial healing (Buhimschi et al, 2010). Further, dorsal skin wounds repaired with skin transplants also show enhanced healing without scarring in MRL (Tolba et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, there have been many reports showing that multiple tissue types in MRL mice display healing responses. These include heart myocardium (Leferovich et al, 2001;Haris Naseem et al, 2007;Alfaro et al, 2008), digits (Chadwick et al, 2007;Gourevitch et al, 2009), articular cartilage (Fitzgerald et al, 2008;Rai et al, 2012), intra-articular fractures (Ward et al, 2008), corneal epithelium (Ueno et al, 2005), CNS stem cells and tissue (Hampton et al, 2004;Baker et al, 2006;Balu et al, 2009;Thuret et al, 2009), central and peripheral nerves (Buckley et al, 2011;Thuret et al, 2012) and myometrial healing (Buhimschi et al, 2010). Further, dorsal skin wounds repaired with skin transplants also show enhanced healing without scarring in MRL (Tolba et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…MRL/MpJs are protected from PTOA and do not 72 develop degenerative joint changes following articular fracture [13]. It has been suggested that 73 MRL/MpJ mice possess an intrinsic ability to regenerate articular cartilage, yet the molecular 74 mechanisms responsible for this phenotype have yet to be revealed [14].…”
mentioning
confidence: 99%
“…In particular, in subsequent studies we have shown that the inbred MRL/MpJ strain, known as the 'superhealer', is protected from PTA and does not develop degenerative joint changes following articular fracture. 4 To briefly summarize the studies in this area, MRL/MpJ mice exhibit a significantly diminished local and systemic inflammatory response following closed articular fracture compared to C57BL/6 mice, and this blunted reaction may explain their relative protection from the development of PTA in this fracture model. In mice that do develop PTA, articular fracture led to increased inflammatory gene expression in the synovium, increased inflammatory protein expression in the synovium, serum and synovial fluid, and increased activated macrophage infiltration of the synovium in association with progression to arthritis.…”
Section: 14-16mentioning
confidence: 99%
“…3 Unlike idiopathic OA, PTA tends to cause significant disability in young and middleaged patients and costs the US economy over $7 billion annually in lost productivity and medical expenses. 2,4 Even with optimal treatment, displaced articular fractures in the lower extremity have a 10 to 20% incidence of PTA. 5 Currently, there are no approved therapies to prevent or address acute PTA, although patients with PTA represent a readily identified population at risk for developing arthritis and thus are ideal to test preventative and therapeutic measures.…”
Section: Introductionmentioning
confidence: 99%